Exploration of the antibacterial and wound healing potential of a PLGA/silk fibroin based electrospun membrane loaded with zinc oxide nanoparticles. Issue 5 (20th January 2021) - Khan, Atta ur Rehman; Huang, Kai; Jinzhong, Zhao; Zhu, Tonghe; Morsi, Yosry; Aldalbahi, Ali; El-Newehy, Mohamed; Yan, Xiaoyu; Mo, Xiumei
Abstract : Zinc oxide nanoparticles (ZnO NPs) are known for their antibacterial, antioxidant, and anti-inflammatory activities. Abstract : Zinc oxide nanoparticles (ZnO NPs) are known for their antibacterial, antioxidant, and anti-inflammatory activities. Moreover, ZnO NPs can stimulate cell migration, re-epithelialization, and angiogenesis. All these attributes are highly relevant to wound healing. Local administration of ZnO NPs to the wound can be achieved through electrospun nanofibers. We hypothesized that the use of poly(lactide- co -glycolic acid) (PLGA)/silk fibroin (SF) nanofiber-based delivery of ZnO would maintain the bioavailability of NPs on the wound area and synchronization with the unique structural features of electrospun nanofibers, could stimulate wound closure, re-epithelialization, collagen deposition, cellular migration, and angiogenesis. In this study, we fabricated PLGA/SF (PS) nanofibrous (NF) membranes with and without ZnO NPs and extensively characterized them for various physicochemical and biological attributes. Scanning electron microscopy (SEM) revealed smooth fibers and ZnO concentration-dependent increase in the fiber diameter. Transmission electron microscopy (TEM) also confirmed the encapsulation of ZnO NPs in the polymer matrix. The successful loading of ZnO was further confirmed by X-ray diffraction. Furthermore, mechanical testing revealed a ZnO concentration-dependent increase in the tensile strength. Moreover, biocompatibility was evaluated through in vitro cell culture. A mild anti-oxidant activity was also noted mainly due to the presence of silk fibroin. In vitro antibacterial tests revealed a ZnO concentration-dependent increase in antibacterial activity and PLGA/SF/3% ZnO (PSZ3) remained completely active against E. coli and S. aureus . More importantly, NF membranes were evaluated for their in vivo wound healing potential. The PSZ3 NF membrane not only facilitated the early wound closure but also remarkably enhanced the quality of wound healing confirmed through histopathological analysis. Re-epithelialization, granulation tissue formation, collagen deposition, and angiogenesis are some of the key parameters significantly boosted by ZnO loaded composite NF membranes. Based on extensive characterization and biological evaluation, the PSZ3 NF membrane has turned out to be a potential candidate for wound healing applications.